Forensic investigation of glass microfragments exposed to heat. (May 2022) - Vörös, Tamás; Takács, Krisztina; Szabó, Attila; Krizsán, Attila
Abstract: The comparative analysis of glasses based on refractive index (RI) is a widely used method in forensic examinations. However, it cannot be directly applied if the control sample has previously been altered by heat or fire, since RI can change significantly in this process. For this reason, the refractive index of the fragments recovered from the perpetrator's clothing can also differ from the control sample recovered after the fire, although they originate from the same source. In the present study, annealing was used as a possible way for the examination of glass microfragments exposed to heat. The appropriate conditions of annealing were investigated first. Then fragments from a toughened and a non-toughened glass were heated in a furnace for various times at 450 and 650 °C and cooled down immediately to model different heat expositions. It resulted in a significant change in the RIs in all cases. These fragments, together with the non-treated samples from the same pane of glasses, were annealed using the optimized parameters. In a similar process, further glasses exposed to real fire were examined. It was found, both in the model experiments and for the fragments exposed to fire, that – regardless of the heat exposure conditions – annealing resulted in the same RI for fragments from the same source, while for different samples different values were observed. Altogether, 11 glasses were examined in 38 experiments, and it was found that annealing combined with refractive index measurement could be a possible way for the examination of heated fragments. The changes in RIs and standard deviations observed during the experiments are consistent with literature data. Highlights: Fire changes the refractive index, precluding direct comparison of glass fragments. Microfragments of 11 glass samples were tested in altogether 38 experiments. Annealing equalized refractive index of pre- and non-treated fragments. Refractive index and standard deviation changes are consistent with former results. Annealing could be an examination method of glass microfragments exposed to heat.